Art Smart: an enhanced content-based filtering algorithm using levenshtein distance for art recommendation system - Buot, Alain Jared N.; Dizon, Kyle-Jie B. 4 0 16; 5 (2023)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology), Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2